What’s in a name? Citizen science in pandemic times - Susanna Priest (Mètode Science Studies Journal: Annual Review)
The phrase citizen science is certainly appealing, especially for many of us who have championed the notion of increasing public engagement in science. Citizen science refers most often to projects in which non-scientists provide some of the labor needed for the collection of scientific data, often in environmental research contexts. This involvement provides volunteer workers in support of science while in turn, ideally, offering rewarding and educational participation opportunities for the volunteers. An early U.S. model for citizen participation has been the Cornell University ornithology laboratory, where the recruitment of a widely dispersed army of bird watchers and other non-scientist citizens continues to assist with bird population research and related studies.